A Journey between Identities: A Story of Education Students' Journey to Ethiopia. Issue 3 (3rd July 2019) - Krivosh, Ludmila
ABSTRACT: The qualitative case study presented in this article describes and analyzes the experiences of Israeli education students, who joined a delegation to Ethiopia last year. This journey opened the doors of Ethiopia to the Ethiopian community's younger generation, most of whom were born in Israel, and to the non-Ethiopian Israelis. During the journey, the participants coped with many challenges and a variety of experiences. They returned home having broken the stereotypes regarding the perception of Ethiopian Jewry, as well as racism, pluralism and relations between the majority and minority groups in Israel. In addition, the Ethiopian participants returned with the renewed identity and the new discourse that had been formed within the group as equal members of Israeli society.